Apakah Profitabilitas Bank Syariah Didorong oleh Faktor Internal? - Laili Maghfiroh; Nur Hajijah; Zainal Musthafa; Umrotul Khasanah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
The purpose of this study is to review and analyze the factors that influence the profitability of Islamic banks in Indonesia. The approach method used in this research is a quantitative approach. The data needed for this research is secondary data which is a report from the Annual Sharia Banking Statistics for the period 2018-2020 obtained and obtained from the Financial Services Authority. Using multiple linear regression analysis techniques (multiple linear regression method). The results show CAR, NPF, FDR and BOPO have a simultaneous influence on the profitability (ROA) of Islamic commercial banks in Indonesia for the 2018-2020 period, and CAR, NPF, and FDR partially have no effect on the profitability (ROA) of Islamic commercial banks in Indonesia for the 2018-2020 period and BOPO partially has a significant negative effect on the profitability (ROA) of Islamic commercial banks in Indonesia for the 2018-2020 period. This research is limited by internal factors that affect the profitability of Islamic commercial banks in Indonesia.